Investigating the importance of emerging disinfection by-products formation through traditional flowsheets and advanced treatment technologies. - Losty, Erin (Cranfield University, 2019)
Chlorine was first used to disinfect drinking water in the US as early as 1908 with other disinfectants, ozone, chlorine dioxide to follow. However, it wasn’t until the 1970’s that Rook discovered a possible link to higher levels of chloroform in drinking water treated with chlorine and inadvertently linked the possibility of precursor material to products of the disinfection process. While the introduction of chlorine to disinfect water has been significant in eliminating pathogens for safe drinking water, it becomes important to safeguard the public against disinfection by-product (DBP) exposure. This thesis intends to give an understanding into the relationship between the control pathway and total DBP formation, giving an insight to the occurrence and the formation for DBPs in drinking water. Emphasis is placed on the natural organic matter characteristics and precursors involved in the formation of DBPs through the treatment process with the use of 3 surface waters. Analysis of 27 traditional and emerging DBPs seek to give a better understanding of the composition of the DBP mixture as a whole, their formation and subsequent minimisation. Comparing two advanced treatment methods, Advanced Oxidative Processes and Nanofiltration with optimal and sub optimal conditions and provide operational advice on minimising DBP formation. AOPs reduced the DBPs and HI more efficiently than nanofiltration but only when high H₂O₂ levels are used. At lower H₂O₂ doses, DBPs increased where as nanofiltration reduced the DBP precursors considerably under optimal and sub-optimal conditions, becoming important in waters with high seasonal variability. Minimising DBPs, specifically THM concentrations has been a priority of water treatment to date, but to reduce the hazard index associated to DBPs would be more beneficial. WHO in vivo generated guideline values exists for only 19 of the 27 DBPs measured, this could potentially limit the ability to understand the impact of the broadest range of emerging DBPs. Over 600 have been discovered and more research is needed to define this mixture and stipulate DBP interactions impacting the hazard index. The key emerging DBPs impacting the HI, using the guideline values, are the brominated and nitrogenated species, BDCAA, BCAA, DCAN and BCAN. Recommendations to monitoring and regulation would be to add these to the current regulatory list by extending HAA5 to HAA9 or as a minimum to include the Br-HAAs. Bromine removal and its subsequent formation of Br-DBPs when not removed effectively, can impact the HI dramatically and, therefore, emphasis for removal is needed. Traditionally upland waters have been the focus due to its high formation of THMs, but it has the lowest HI throughout. Lowland lake, with the highest bromine levels generated the highest HI, consideration is needed to better minimise DBP formation.
PhD in Water including Design
Keywords: Natural organic matter; advanced oxidative processes; nanofiltration; emerging DBPs; hazard index